We have been given that [tex]m=6x+5[/tex]. We are asked to write [tex](6x + 5)^2-10 =-18x-15[/tex] in terms of m.
First of all, we will factor [tex]-3[/tex] from right side of equation as:
[tex](6x + 5)^2-10 =-3\cdot 6x-3\cdot 5[/tex]
[tex](6x + 5)^2-10 =-3( 6x+5)[/tex]
Now we will substitute [tex]m=6x+5[/tex] in our equation as:
[tex](m)^2-10 =-3(m)[/tex]
[tex]m^2-10 =-3m[/tex]
Upon adding [tex]3m[/tex] on both sides, we will get:
[tex]m^2+3m-10 =-3m+3m[/tex]
[tex]m^2+3m-10 =0[/tex]
Therefore, the equation [tex]m^2+3m-10 =0[/tex] is equivalent to [tex](6x + 5)^2-10 =-18x-15[/tex] in terms of m.